Tcap Deficiency in Zebrafish Leads to ROS Production and Mitophagy, and Idebenone Improves its Phenotypes - Lv, Xiaoqing; Zhang, Rui; Xu, Ling; Wang, Guangyu; Yan, Chuanzhu; Lin, Pengfei (Frontiers in Cell and Developmental Biology, 2022)
Limb-girdle muscular dystrophy 2G (LGMD2G) is a subtype of limb-girdle muscular dystrophy. However, the disease's mechanisms are still not fully understood, and no established therapeutic targets have been found. Using a morpholino-based knockdown approach, we established an LGMD2G zebrafish model. In this study, we found that the ROS level increased in LGMD2G zebrafish. The expression of the mitophagy-related protein BNIP3L, LC3A-II/LC3A-I, and LAMP1 were increased in LGMD2G zebrafish. The oxygen consumption rate and citrate synthase expression was significantly decreased. Thus, mitophagy was presumed to be involved in the LGMD2G to reduce ROS levels. Then, we administered vitamin C, coenzyme Q10, idebenone, metformin, or dexamethasone to rescue LGMD2G in zebrafish. Idebenone reduced the curly tail phenotype and ROS level. Also, it reduced BNIP3L expression in LGMD2G zebrafish models and improved their motor function. In conclusion, mitophagy might be involved in the LGMD2G, and idebenone ameliorated LGMD2G by downregulating ROS level.